PENGARUH E-COMMERCE DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA KERIPIK DONA BATURAJA (STUDI KASUS PADA PENJUALAN DI APLIKASI SHOPEE) - Ike Yuliantika; Rosmala Dewi; Nourma Wulanda; M. Agus Kurniawan; Dyah Ayu Putriani (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
This study aims to analyze the influence of e-commerce and productdesign on the purchasing decisions of Keripik Dona Baturaja throughthe Shopee application. Data collection was carried out by distributingquestionnaires to 80 respondents. The data analysis technique usedwas multiple linear regression. The results showed that partially, the ecommercevariable had a significant effect on purchasing decisions,with a t-value of 5.693. Likewise, the product design variable also hada significant effect, with a t-value of 5.914 and a significance value of0.200 (α > 0.05). Simultaneously, e-commerce and product designjointly had a significant influence on purchasing decisions, with an Fvalueof 101.092. The coefficient of determination (R²) was 0.724,indicating that 72.4% of the variation in purchasing decisions wasinfluenced by e-commerce and product design, while the remaining27.6% was influenced by other variables outside the scope of thisstudy, such as product quality, price, and promotion (Buchari Alma,2018:96).